2016
DOI: 10.1017/s0025315416000734
|View full text |Cite
|
Sign up to set email alerts
|

Assortative epibiosis of leatherback, olive ridley and green sea turtles in the Eastern Tropical Pacific

Abstract: Sea turtles host a diverse array of epibionts, yet it is not well understood what factors influence epibiont community composition. To test whether epibiont communities of sea turtles are influenced by the hosts’ nesting or foraging habitats, we characterized the epibiota of leatherback, olive ridley and green turtles nesting at a single location on the Pacific coast of Costa Rica. We also compared the epibiota of these turtles to conspecific populations nesting elsewhere in the East Pacific. If epibiont commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Species number in a single sample varied between 11 and 111 taxa (including taxa observed outside the counts) ( Fig 4A), and the median from the same area was generally lower in the skin samples (26) than in the carapace samples (51). Among carapace samples, the South African samples were the most taxa-abundant, whereas the lowest number of taxa characterized Florida and some of the Croatian samples ( Fig 4A).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Species number in a single sample varied between 11 and 111 taxa (including taxa observed outside the counts) ( Fig 4A), and the median from the same area was generally lower in the skin samples (26) than in the carapace samples (51). Among carapace samples, the South African samples were the most taxa-abundant, whereas the lowest number of taxa characterized Florida and some of the Croatian samples ( Fig 4A).…”
Section: Plos Onementioning
confidence: 99%
“…Other sea turtle species such as olive ridley and green turtle show a different feeding behavior and have a different diet [25], which may influence the epizoic diatom species composition. Robinson et al [51] observed that the macro-epibiont diversity of nesting sea turtles is partially linked to the diversity of their foraging habitats. Thus, sea turtle species with more diverse foraging areas should have more diverse epibiont communities.…”
Section: Plos Onementioning
confidence: 99%
“…Those organisms that live on the surfaces of other organisms are referred to as epibionts [3], a grouping of diverse taxa with a wide range of life-histories, physiological tolerances, and mechanisms for attaching to their host [4]. It is therefore not surprising to discover that epibiont communities vary among different host species [5,6], populations [7], and even between different body-areas on a single host [8,9]. To understand why this variation occurs requires knowledge of the factors driving spatial variation in the distribution of epibionts, both on the scale of an ocean or a host’s body.…”
Section: Introductionmentioning
confidence: 99%
“…Sea turtles often harbour complex communities of epibionts [ 1 , 2 , 3 ]. These epibiont communities can provide valuable insights into the hosts’ behaviour [ 4 , 5 ] and health [ 6 , 7 ]; however, most studies on sea turtle epibiosis have focused exclusively on macro-epibiota.…”
Section: Introductionmentioning
confidence: 99%